Game Edukasi Pengenalan Anatomi Manusia Berbasis Android Untuk Anak Menggunakan Metode Role Playing - Ummu Khairiah (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
To make it easier for children not to be lazy and bored in the learning process especially in learning HumanAnatomy in English, the research will be made interactive and interesting. For this reason, this application wascreated for Human Anatomy learning aids in English using Construct 2. Construct 2 is a 2D game engine forHTML5 developed by Scirra Ltd, a start-up company based in London. This game engine was developed with theconcept of behavior & attachments so that the logic in the game can be built without having to type one line ofcoding, just drag and drop it. With the rapid development of technology today, educational games can not onlybe enjoyed through PCs, but can also be enjoyed through Android. Media game learning will help children makeit easier to recognize and memorize human anatomy in English. Children will be easier to remember thematerial delivered by the game because it is presented in a pleasant appearance.